Sulfonation and anticoagulant activity of botryosphaeran from Botryosphaeria rhodina MAMB-05 grown on fructose - Mendes, Simone Ferreira [UNESP]; dos Santos, Osvaldo [UNESP]; Barbosa, Aneli M.; Vasconcelos, Ana Flora D. [UNESP]; Aranda-Selverio, Gabriel [UNESP]; Monteiro, Nilson K. [UNESP]; Dekker, Robert F. H.; Pereira, Mariana Sa; Tovar, Ana Maria F.; de Souza Mourao, Paulo A.; Corradi da Silva, Maria de Lourdes [UNESP] (Elsevier B.V., 2009)
Botryosphaeran (EPS(FRU)), an exopolysaccharide of the beta-(1 -> 3,1 -> 6)-D-glucan type with 31% branching at C-6, is produced by the fungus Botryosphaeria rhodina MAMB-05 when grown on fructose as carbon source. Botryosphaeran was derivatized by sulfonation to induce anticoagulant activity. The effectiveness of the sulfonation reaction by chlorosulfonic acid in pyridine was monitored by the degree of substitution and FT-IR analysis of the sulfonated EPS(FRU) (once sulfonated, EPS(FRU SULF); and re-sulfonated, EPS(FRU RESULF)). Activated partial thromboplastin time (APTT) and thrombin time (TT) tests of EPS(FRU RESULF) indicated significant in vitro anticoagulant activity that was dose-dependent. EPS(FRU) did not inhibit any of the coagulation tests. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Botryosphaeria rhodina MAMB-05; Exopolysaccharide; beta-(1 -> 3,1 -> 6)-D-Glucan; Sulfonation; Anticoagulant activity